2015
DOI: 10.5114/fn.2015.49976
|View full text |Cite
|
Sign up to set email alerts
|

Original article Sertraline and curcumin prevent stress-induced morphological changes of dendrites and neurons in the medial prefrontal cortex of rats

Abstract: A b s t r a c t Stress induces structural and behavioral impairments. The changes in dendrites and neurons are accompanied by impairments in the tasks mediated by the medial prefrontal cortex (mPFC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 41 publications
(65 reference statements)
2
4
0
Order By: Relevance
“…It was the result of their constant changing in response to neuronal activity (e.g., chronic stress; Segal et al, 2000). Moreover, the present study in parallel with other reports demonstrated that curcumin had protective effects on the number of changes of neurons of the prefrontal cortex and hippocampus reduced by stress (Noorafshan et al, 2014, 2015). Various studies have explained different protective mechanisms of the treatment for curcumin in various neurological disorders.…”
Section: Methodssupporting
confidence: 91%
“…It was the result of their constant changing in response to neuronal activity (e.g., chronic stress; Segal et al, 2000). Moreover, the present study in parallel with other reports demonstrated that curcumin had protective effects on the number of changes of neurons of the prefrontal cortex and hippocampus reduced by stress (Noorafshan et al, 2014, 2015). Various studies have explained different protective mechanisms of the treatment for curcumin in various neurological disorders.…”
Section: Methodssupporting
confidence: 91%
“…Sun et al (2013[25]) disclosed that CUR could also recover learning and memory in senescence-accelerated mice. Similarly, our previous studies revealed that CUR could play protective roles in rat prefrontal cortical neurons in different pathological conditions (Noorafshan et al, 2015[20]). SD could diminish the spatial memories and affect the mPFC structure.…”
Section: Discussionsupporting
confidence: 57%
“…To estimate and calculate the average of striatal dendritic length per neuron, two essential quantities were required for evaluation: the first one was the number of neuronal cell body via an optical dissector method, and the second one was the crossings between oriented cycloid and dendrite axes. As a final point, average striatal dendritic length per neuron was calculated, using the unbiased stereological formula (Noorafshan, Abdollahifar, Karbalay‐Doust, Asadi‐Golshan, & Rashidian‐Rashidabadi, )…”
Section: Methodsmentioning
confidence: 99%